ENT 530 Case Study (Go and Grab (Kiosk) / Nadia Hanafi ... [et al.] - Hanafi, Nadia; Samsudin, Siti Nur Lukluah; Sharif, Nurhayati; Mohd Sarijil, Mohd Zulki (2018)
Understanding the marketplace, the wider industry and competition is necessary so that the specific business objectives of the project can be well-defined and, more importantly, meet a genuine need, or anticipated need, within the market to which the end-product will be targeted. For example projects is in small organisations marketplace such as SME business may be a small internal team or department but the concept of understanding them and their objectives is still the same and important.